Optimizing Inorganic Carbon Sequestration and Crop Yield With Wollastonite Soil Amendment in a Microplot Study - Haque, Fatima; Santos, Rafael M.; Chiang, Yi Wai (Frontiers in Plant Science, 2020)
Carbon dioxide (CO2) is a major greenhouse gas, and its concentration in the atmosphere is increasing continuously, hence there is an urgent need to reduce its level in the atmosphere. Soils offer a large natural sink to store CO2. This study focuses on sequestering CO2 in the agricultural soils as inorganic carbon, which can be accomplished by adding alkaline-earth silicates. Wollastonite is used in this study as a soil amendment, to sequester CO2 via the geochemical route of mineral carbonation. The first objective of the present study was to evaluate the effect of mixing a wide range of dosages of wollastonite, as a soil amendment, on the growth performance of two leguminous plants frequently used in agricultural sector: soybean and alfalfa. The plants were grown with different wollastonite dosages (3-20 kg·m-2 for soybean and 3-40 kg·m-2 for alfalfa), for a duration of 14 weeks in a microplot experiment in Ontario, Canada. The second objective was to find evidence of enhanced weathering of wollastonite in soil, in addition to the augmentation of inorganic carbon content in soil. For this, mineralogical assessment of the soils was performed using XRD and SEM-EDS analyses. Wollastonite increased the soybean yield by two-fold in the plot amended with 10 kg·m-2. At all dosages, wollastonite increased the alfalfa growth in terms of height and above-ground biomass dry weight, as well as root biomass. The rate of CO2 sequestration, at optimum wollastonite dosage, reached 0.08 kg CO2·m-2·month-1. XRD and SEM-EDS analyses indicated accumulation of calcite in wollastonite-amended soil and formation of other weathering products. The results obtained from this study help to understand the impact of wollastonite soil amendment on agronomy, and will aid in implementing such negative emissions technology by informing farmers and industry alike that the use of wollastonite contributes toward global climate change mitigation while supporting crop yield. The findings of this study add to the existing body of knowledge on enhanced weathering as an atmospheric CO2 removal technology, providing further evidence that wollastonite weathering in agricultural soils can lead to significant capacity for CO2 sequestration as inorganic carbon, while concurrently promoting plant growth.